2014
DOI: 10.1155/2014/305823
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Solar Drying of Ginger (Zingiber officinale): Emprical Modelling, Drying Characteristics, and Quality Study

Abstract: Drying is a simultaneous heat and mass transfer energy intensive operation, widely used as a food preservation technique. In view of improper postharvest methods, energy constraint, and environmental impact of conventional drying methods, solar drying could be a practical, economical, and environmentally reliable alternative. In the present paper applicability of mixed mode solar cabinet dryer was investigated for drying of commercially important and export oriented ginger. Freshly harvested ginger slices were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
2
37
0
1
Order By: Relevance
“…However, the moisture removing rate is also dependent on the ease of heat transfer. Forced convection drying system has been reported to be best suitable for faster drying as the value of the coefficient of convective heat transfer associated with them is more than the natural convection drying (Azharul Karim & Hawlader, 2005;Deshmukh et al, 2013Deshmukh et al, , 2014. From Figure 4, it has been observed that the values of convective heat transfer coefficient decrease with the progression of drying months, that is, June, July, and August 2016.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the moisture removing rate is also dependent on the ease of heat transfer. Forced convection drying system has been reported to be best suitable for faster drying as the value of the coefficient of convective heat transfer associated with them is more than the natural convection drying (Azharul Karim & Hawlader, 2005;Deshmukh et al, 2013Deshmukh et al, , 2014. From Figure 4, it has been observed that the values of convective heat transfer coefficient decrease with the progression of drying months, that is, June, July, and August 2016.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…About half of the total production of Asparagus is being consumed as white and red Asparagus, whereas the remaining 30% is converted into dry Asparagus for medicinal purposes, and 20% is used as seed material (Deshmukh, Varma, Yoo, & Wasewar, 2014).…”
mentioning
confidence: 99%
“…The moisture content decrease after 20, 40, 60, 80 and 100 minutes. From the experiment was done above, which have strong correlation with the drying processes of other food products [5,7,8,13,14]. One of the high-quality factor from the consumer's point view was the changing of the colour after dried [14].…”
Section: Carrageenan Extractionmentioning
confidence: 99%
“…One of disadvantage of this method, seaweed is not good in quality and also the problem of hygienic. The product gets contaminated from dust, insects, rodents, and other animals, which seriously lowering the food quality [5]. Drying kinetics in seaweeds was also studied under these following pre-treatments: open drying and drying at various temperature from 40-90 °C [6].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 revealed that the drying rate of Safed Musli dried in T1, T2 and T3 trays of domestic solar dryer integrated with reflector varied from 1.3384 to 0.0047, 1.2308 to 0.0224 and 1.2214 to 0.0254 gm/100gm bdm min, respectively Figure 3 revealed that the drying rate of Safed Musli dried in T1, T2 and T3 trays of domestic solar dryer integrated with reflector varied from 1.3384 to 0.0047, 1.2308 to 0.0224 and 1.2214 to 0.0254 gm/100gm bdm min, respectively and average drying rate was found to be 0.5526, 0.54103 and 0.53455 gm/100gm bdm min, respectively. Deshmukh et al, 2014).…”
Section: No Load Testing Of Domestic Solar Dryer With Reflectormentioning
confidence: 99%